High frequency financial econometrics : recent developments - Bauwens, Luc (Springer, 2017)
This exciting volume presents cutting-edge developments in high frequency financial econometrics, spanning a diverse range of topics: market microstructure, tick-by-tick data, bond and foreign exchange markets and large dimensional volatility modelling. The chapters on market microstructure deal with liquidity, asymmetries of information, and limit order aggressiveness in pure limit order book markets. The chapters on tick-by-tick data present statistical techniques for the analysis of the discrete nature of price movements, the intraday seasonal patterns of financial durations, and the joint probability law of prices, volume and durations. Bond markets are brought into focus through the analysis of macroeconomic announcements in the future bond market as a function of the business cycle. Exchange markets are examined from two perspectives: the study of the impact of information arrival on exchange rate volatility and the uncovering of chartist patterns in the euro/dollar exchange rate. Last, dynamic modelling of large dimensional covariance matrices is also presented. Shedding light on some of the most relevant open questions in the analysis of high frequency data, this volume will be of interest to graduate students, researchers and industry professionals.